Enhancing students' knowledge and competency through Accurate software training: SMK Muhammadiyah 9 in South Jakarta - Rieke Pernamasari; Sri Purwaningsih; Giawan Nur Fitria (EQUATOR SINAR AKADEMIA, 2023)
The advancement of technology and the increasingly complex challenges in the working world have prompted accounting vocational school students to acquire sufficient knowledge and competency in using Accurate software. The purpose of this activity is to enhance the competence and hard skills knowledge of students at SMK Muhammadiyah 9 in South Jakarta. Through this community service activity, it is expected to improve students' abilities in using Accounting Software, specifically Accurate version 5, to generate financial reports. The training was conducted over 2 days on February 14 and 15, 2022, with a total of 59 student participants using Google Meet. It started with an introduction by the community service team, followed by completing a pre-test, database creation using basic setup, and practical exercises solving case studies using Accurate software specifically for trading companies. The outcome of this community service is an increased understanding, ability, and competency of the training participants in using Accurate software, which will assist teachers and students in the learning process at school and serve as preparation for their future entry into the workforce